Coretax Application Usage by Local Government Expenditure Treasurers: An Evaluation Based on Technology Acceptance Model - Sutaryo Sutaryo; Y Anni Aryani; Taufiq Arifin; Doddy Setiawan; Evi Gantyowati; Payamta Payamta; Isna Putri Rahmawati; An Nurrahmawati; Muhammad Alif Nur Irvan (Pajak dan Manajemen Keuangan, 2025)
The study aims to evaluate the adoption of the Coretax system by government expenditure treasurers using the Technology Acceptance Model (TAM). We assesses the factors influencing users' attitudes and intentions toward using new technology. Primary data from local government public service agencies in Karanganyar and Wonogiri regencies are collected by using questionnaire, analyzed with linear regression and path analysis. Our analysis reveals that perceived usefulness and behavioral intention are scored high, indicating that the treasurers find Coretax beneficial and are strongly inclined to continue using it. However, perceived ease of use and attitude toward use showed moderate to high ratings, indicating room for improvement in terms of ease of use and user comfort. Regression analysis found that perceived ease of use significantly affects perceived usefulness, attitude toward use, and behavioral intention. However, perceived usefulness and attitude toward use did not significantly influence behavioral intention. The findings suggest that the ease of use of Coretax plays a more crucial role in shaping the treasurers' behavioral intentions than perceived usefulness or affective attitude. This study providing insights into key determinants affecting user intentions and offering empirical foundations for developing training policies, system design improvements, and implementation strategies tailored to the public sector's needs. The findings of this research are also expected to contribute to offer practical implications for strengthening national tax digitalization reforms.